Passive Smoke Exposure as a Risk Factor for Oral Clefts—A Large International Population-Based Study - Kummet, Colleen M. (Am J Epidemiol, 2016)
Maternal cigarette smoking is a well-established risk factor for oral clefts. Evidence is less clear for passive (secondhand) smoke exposure. We combined individual-level data from 4 population-based studies (the Norway Facial Clefts Study, 1996–2001; the Utah Child and Family Health Study, 1995–2004; the Norwegian Mother and Child Cohort Study, 1999–2009; and the National Birth Defects Prevention Study (United States), 1999–2007) to obtain 4,508 cleft cases and 9,626 controls. We categorized first-trimester passive and active smoke exposure. Multivariable logistic models adjusted for possible confounders (maternal alcohol consumption, use of folic acid supplements, age, body size, education, and employment, plus study fixed effects). Children whose mothers actively smoked had an increased risk of oral clefts (odds ratio (OR) = 1.27, 95% confidence interval (CI): 1.11, 1.46). Children of passively exposed nonsmoking mothers also had an increased risk (OR = 1.14, 95% CI: 1.02, 1.27). Cleft risk was further elevated among babies of smoking mothers who were exposed to passive smoke (OR = 1.51, 95% CI: 1.35, 1.70). Using a large pooled data set, we found a modest association between first-trimester passive smoking and oral clefts that was consistent across populations, diverse study designs, and cleft subtypes. While this association may reflect subtle confounding or bias, we cannot rule out the possibility that passive smoke exposure during pregnancy is teratogenic.